(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to find out: "The impact of historical documentaries on collectingLiterary fifth grade students1- There is no statistically significant difference at the significance level (0, 05) between the mean scores ofFemale students of the experimental group who study history according to documentariesbetween the mean scores of the students of the control group who study the subjectThe same as the traditional method in the achievement test.The researchers chose an experimental design with partial control of two groups, one experimentalAnd the other is a control group, and the two research groups (experimental and control) were rewarded, and the researcher choseThe research community was intentionally from the second Rusafa district, and the school (Integrity for Girls) was chosen.Intentionally, two divisions were chosen by the simple random method from the fifth grade divisionLiterary, one of them represented the experimental group studying history based on filmsHistoric and the number of students (30) students. The second was the control group(30) students studying the same subject in the traditional way; Thus, the number of peopleThe research sample (60) students included the first three chapters of the book (European History).Hadith and Contemporary) to be taught for the academic year 2012-2013.The researcher studied the two research groups herself, and to measure the level of achievement of the students, she preparedThe researcher took a post achievement test consisting of (35) items of multiple choice type.